2015
DOI: 10.1016/j.ibiod.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of granular sludge with hypersaline oily wastewater

Abstract: a b s t r a c tThe time required to stabilise mature aerobic granules is rather variable. In addition, cultivation time and the structural characteristics of granules seem to be related to the nature of wastewater influent. Granular sludge has been used for the treatment of several industrial wastewaters, but nothing has been reported about wastewater characterized by the simultaneous presence of hydrocarbons and high chloride concentration. In this work, the authors analysed the granulation process and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 36 publications
4
26
2
2
Order By: Relevance
“…AGS have been successfully implemented for the treatment of both municipal and industrial wastewater. The literature studies demonstrated that aerobic granules feature a compact and thick structure, thus ensuring a great ability to withstand adverse environmental conditions, such as loading variation, obtaining very high effluent quality at the same time [17][18][19][20]. Indeed, the granular sludge features very high settling ability and allows to maintain higher biomass concentrations, thus reducing the plant footprint [21].…”
Section: Introductionmentioning
confidence: 99%
“…AGS have been successfully implemented for the treatment of both municipal and industrial wastewater. The literature studies demonstrated that aerobic granules feature a compact and thick structure, thus ensuring a great ability to withstand adverse environmental conditions, such as loading variation, obtaining very high effluent quality at the same time [17][18][19][20]. Indeed, the granular sludge features very high settling ability and allows to maintain higher biomass concentrations, thus reducing the plant footprint [21].…”
Section: Introductionmentioning
confidence: 99%
“…A significant consumption, however, was observed during the famine phase in which substrate is present in limiting concentrations and bacteria utilize EPS as carbon and energy source for endogenous respiration (Zhu et al, 2012a;Corsino et al, 2015). However, no information was available on how the EPS characterization under different lengths of the famine phase affects granular stability in treating actual high-strength wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been reported that EPS contributes to the adsorption and adhesion of metal ions and organic pollutants because of the hydrophobic and hydrophilic regions in their structures (Jia et al, 2016). Microorganisms growing in unfavorable conditions produce additional EPS to protect themselves by balancing osmotic pressure (Tourney et al, 2009;Corsino et al, 2015). Nowadays, many researchers have reported the importance of EPS in forming granules and biofilms.…”
Section: Introductionmentioning
confidence: 99%